Coach and athlete perspectives on talent transfer in Paralympic sport - Dehghansai, N.; Mazhar, A.; Baker, J. (Adapted Physical Activity Quarterly, 2023)
Research pertaining to the experiences and motives of Paralympic athletes who transfer between sports is scant. This study aimed to address this gap through semistructured interviews with Canadian Paralympic coaches (n = 35) and athletes (n = 12). Three higher-order themes of "alternative to retirement," "career extension," and "compatibility" were identified. The subthemes of "psychobehavioral" and "physical and physiological" (from the higher-order theme of alternative to retirement) captured reasons leading to transfer, which are similar to reasons athletes may consider retirement. The subthemes of career extension—"better opportunities" and "beneficial outcomes"—shed light on factors that contributed to the withdrawal of negative experiences and reinforcement of positive outcomes associated with transferring sports. Last, compatibility had three subthemes of "resources," "sport-specific," and "communication," which encapsulated factors athletes should consider prior to their transfer. In conclusion, the participants highlighted the importance of transparent and effective communication between athletes and sports to align and establish realistic expectations for everyone involved.